Orexinergic System in Neurodegenerative Diseases - Wang, Qinqin; Cao, Fei; Wu, Yili (Frontiers in Aging Neuroscience, 2021)
Orexinergic system consisting of orexins and orexin receptors plays an essential role in regulating sleep–wake states, whereas sleep disruption is a common symptom of a number of neurodegenerative diseases. Emerging evidence reveals that the orexinergic system is disturbed in various neurodegenerative diseases, including Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD), and multiple sclerosis (MS), whereas the dysregulation of orexins and/or orexin receptors contributes to the pathogenesis of these diseases. In this review, we summarized advanced knowledge of the orexinergic system and its role in sleep, and reviewed the dysregulation of the orexinergic system and its role in the pathogenesis of AD, PD, HD, and MS. Moreover, the therapeutic potential of targeting the orexinergic system for the treatment of these diseases was discussed.